Higher spherical equivalent refractive errors is associated with slower axial elongation wearing orthokeratology. Issue 1 (February 2016) - Fu, Ai-Cun; Chen, Xing-Lin; Lv, Yong; Wang, Shu-Lin; Shang, Li-Na; Li, Xiu-Hong; Zhu, Yu
Abstract: Purpose: To investigate the relationship between axial length (AL) increase and baseline spherical equivalent refractive errors (SER) in myopic children wearing orthokeratology contact lenses (OK). Methods: One hundred fifteen Chinese (115 right eyes) children wearing OK were enrolled in this cohort study. Gender, age, baseline SER, corneal power, corneal astigmatism, and AL at baseline and 2 years after wearing OK were collected. Univariate analysis and trend test were used to estimate the relationship between change in AL and baseline SER. Results: After univariate analysis, a statistically significant relationship was found between change in AL and baseline SER ( β  = 0.061, 95% CI: 0.015–0.111, P  = 0.015). In the trend test, after adjusting for potential confounders, higher SER was associated with smaller increases in AL ( P trend = 0.041). Conclusions: The SER at baseline was associated with AL growth in myopic children wearing OK. The higher SER was associated with slower AL growth and control the development of myopia.